Histoire des Archives de la ville de Lausanne, des origines à aujourd'hui (1401-1986) - Coutaz, Gilbert (Économat de la Ville, 1986)

La prolongation de la durée d'un dépôt, à travers l'expérience du Calvados - Bernard, Gildas (Gazette des archives, 1980)

Les services extérieurs du Trésor : leur histoire et leurs attributions actuelles - Roumagnac, Charles (Gazette des archives, 1980)
The " external services " of the Treasury : their history and present attributions. After a historical survey, the author explains the attributions of the Treasury services in the départements, and describes the usual organisation of the Trésorerie générale in a département. He observes that these services are in rapid evolution, a consequence of the general economic evolution and the introduction of computers.